Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada Pariwisata 4.0 di Madura - Putra, Rendy Pratama; Wildan, Muhammad Alkirom (Jurnal Ilmiah Pariwisata, 2023)
This study aims to determine the effect of organizational culture and organizational commitment on employee performance in tourism 4.0 in Madura. This type of research is a quantitated qualitative research. The data collection technique was by distributing questionnaires using a Likert scale from 1 to 5. The sampling technique used saturated sampling because the population and sample in this study were the same, namely as many as 70 employees working in the tourism industry in Bangkalan Regency. The results of the study show that organizational culture has no significant effect on employee performance variables, because the more conducive organizational culture that is applied to Tourism 4.0 in Madura does not necessarily improve the performance of its employees who tend not to be creative. Then organizational commitment has a significant effect on employee performance, because the desire of employees to continue working in accordance with organizational goals without coercion, reflects a sense of pride in employees so that they do not need to be monitored with a low level of resignation. The advice that can be given is that it is hoped that tourism managers in Madura will always improve the rules that must be considered by their employees. Keywords: Organizational Culture, Organizational Commitment, Performance